Les Misérables: An analysis of low SWB across the world - Melios, Georgios; Laffan, Kate; Kudrna, Laura; Dolan, Paul (Frontiers in Psychology, 2023)
Global trends indicate that the prevalence of low subjective well-being is on the rise, but that not all regions are equal in terms of both absolute levels and their trajectories. In this paper, we explore the relative importance of individual- and country-level factors in predicting low SWB. Put differently, we ask if a person found themselves behind a veil of ignorance, should they want to know who they will be or what country they live in to better understand their risk of having low well-being? To answer this question, we leverage data from the most extensive well-being survey in the world - the Gallup World Poll. We explore people's likelihood of reporting low evaluative well-being (that their life is close to the worst possible life on the Cantril ladder and low experiential well-being (reporting having felt angry, sad, stressed and worried for most of the day yesterday). Using multilevel models on both measures, we show that individual factors - who you are - have the greatest explanatory power across both measures, but that country factors are almost four times more important in explaining the variation in low evaluative well-being than low experiential well-being around the world. We also present evidence that individual and country-level factors interact, suggesting that a complex system of people and places determines people's likelihood of reporting low SWB.